Novel mutations in NLGN3 causing autism spectrum disorder and cognitive impairment. Issue 11 (29th July 2019) - Quartier, Angélique; Courraud, Jérémie; Thi Ha, Thuong; McGillivray, George; Isidor, Bertrand; Rose, Katherine; Drouot, Nathalie; Savidan, Marie‐Armel; Feger, Claire; Jagline, Hélène; Chelly, Jamel; Shaw, Marie; et al.
Abstract: The X‐linked NLGN3 gene, encoding a postsynaptic cell adhesion molecule, was involved in a nonsyndromic monogenic form of autism spectrum disorder (ASD) by the description of one unique missense variant, p.Arg451Cys (Jamain et al. 2003). We investigated here the pathogenicity of additional missense variants identified in two multiplex families with intellectual disability (ID) and ASD: c.1789C>T, p.Arg597Trp, previously reported by our group (Redin et al. 2014) and present in three affected cousins and c.1540C>T, p.Pro514Ser, identified in two affected brothers. Overexpression experiments in HEK293 and HeLa cell lines revealed that both variants affect the level of the mature NLGN3 protein, its localization at the plasma membrane and its presence as a cleaved form in the extracellular environment, even more drastically than what was reported for the initial p.Arg451Cys mutation. The variants also induced an unfolded protein response, probably due to the retention of immature NLGN3 proteins in the endoplasmic reticulum. In comparison, the c.1894A>G, p.Ala632Thr and c.1022T>C, p.Val341Ala variants, present in males from the general population, have no effect. Our report of two missense variants affecting the normal localization of NLGN3 in a total of five affected individuals reinforces the involvement of the NLGN3 gene in a neurodevelopmental disorder characterized by ID and ASD. Abstract : Our study reports the characterization of two novel missense variants in NLGN3, causing a nonsyndromic form of ID associated with autistic manifestations. The variants studied lead to an absence/decrease of membrane localization of NLGN3, its retention in the endoplasmic reticulum (ER) and induction of a cellular response related to ER stress.